Motor Control and Learning - Latash, Markus.; Latash, Markus.; Lestienne, Francis.; Lestienne, Francis. (Springer US : Imprint: Springer, 2006)
Motor Control and Learning focuses on the effects of development, aging, and practice on the control of human voluntary movement. These issues have been at the center of attention of the motor control community, but no book until now has addressed all of these issues under one cover in the context of contemporary views on the control of human voluntary movement. This book emphasizes the links between progress in basic motor control research and applied areas such as motor disorders and motor rehabilitation. Contributors are established scientists in the areas of both theoretical/experimental motor control and its applications. The chapters focus more on large, general issues than on their particular research. As a result, Motor Control and Learning is relevant to both professionals in the areas of motor control, movement disorders, and motor rehabilitation, and to students who are starting their careers in one of these actively developed areas. Dr. Mark L. Latash is Professor of Kinesiology at the Pennsylvania State University. Dr. Francis G. Lestienne is Professor and Director of the Center for Science and Technology in Physical Activity and Sports at the Université de Caen Basse-Normandie, France.